If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 13) = 54 Reorder the terms: x + (13 + x) = 54 Remove parenthesis around (13 + x) x + 13 + x = 54 Reorder the terms: 13 + x + x = 54 Combine like terms: x + x = 2x 13 + 2x = 54 Solving 13 + 2x = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2x = 54 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = 54 + -13 2x = 54 + -13 Combine like terms: 54 + -13 = 41 2x = 41 Divide each side by '2'. x = 20.5 Simplifying x = 20.5
| x=0.8x+2.8 | | 4a^2-144=0 | | 6p=228 | | 5-x-2=3 | | x=6x+3x | | 10x+6=2x+44 | | 6+4(1+3x)=7(x-5) | | 55=-7x+6 | | -1.4(-4p-1)+4.4p= | | 9y-3=7y+1 | | 4x+7=7(x+1)-3x | | 26-(3x-10)=6 | | 4-36= | | -4+-61= | | -1.4(-4p-1)+4.4= | | d+9-90=-5 | | -2(4-3z)-7=6(z+1) | | 2x-(24-x)=-6 | | 20x+5=125 | | 2(5t-1)=10-2t | | x(x+1)=552 | | 4(x-2)-6x=35 | | 3x-x=30 | | 4x-3=28x+3 | | 3(2x+1)-8= | | 86k-95=-1643 | | 6x-61=47 | | 4(w-3)=2(w-1)+(2w-10) | | 10x-1=8x+16 | | 7y-15y=-32-40 | | 2(x-4)=3(x-2) | | -3t^2-7t-8=0 |